Tantangan dan Peluang Teknologi Digital Bagi Eksistensi Budaya Kalwedo dan Implikasinya dalam Dunia Pendidikan - Febrilien Matresya Matulatuwa; Amos Lekiwona (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
In the era of technology that continues to develop, the people of Southwest Maluku who live in areas classified as 3T (Underdeveloped, Frontier and Outermost) face significant challenges related to the cultural influence offered through online media which has become a necessity in people's lives. The purpose of this research is to discuss the importance of understanding the challenges and opportunities of digital technology for the cultural existence of the Moa people. The method used in this study is qualitative because the data generated is descriptive in nature. The results of the study relate to the challenges and opportunities of digital technology for the existence of kalwedo culture in the context of the life of the Moa community which has experienced a significant decline, caused by foreign culture offered through digital technology which is more popular with almost all young people who are the successors for sustainable regional development. People no longer respect each other, no longer build direct communication and even people who are close feel far and people who are far feel close. This kind of living condition was never imagined by the ancestors who tried to create kalwedo culture as the identity of the Moa community in particular but also the people of Southwest Maluku in general. The world of education is also unable to design a curriculum that can answer the challenge of the fading value of kalwedo culture as something that needs to be preserved through the learning process